Characterization of thermophilic fungi producing extracellular lignocellulolytic enzymes for lignocellulosic hydrolysis under solid-state fermentation - Saroj, Paramjeet; P, Manasa; Narasimhulu, Korrapati (Bioresources and bioprocessing, 2018)
Background Thermotolerant lignocellulolytic enzymes have become a subject of interest in industrial processes due to their ability to degrade lignocellulosic polysaccharides. Development of cost-effective, large-scale screening for production of desirable enzymes by thermophilic fungi is a challenge. The present investigation focused on isolating, screening, and identifying industrially relevant thermophilic producers of lignocellulolytic enzymes from various locations in the Warangal district, Telangana, India. Results Fifteen thermophilic fungi were isolated from soil on their ability to grow at 50 °C and were screened for their activity of cellulase, hemicellulase, and lignin degradation based on holo zone around colonies. The appearance of the black color zone of diffusion in esculin agar is a positive indication for the β-glucosidases activity test. Out of fifteen isolates, Aspergillus fumigatus JCM 10253 have shown as a potential producer of extracellular enzymes for lignocelluloses degradation showing higher activity for cellulase (EI 1.50) as well as β-glucosidase (4 mg/mL), simultaneously for xylanase (EI 1.18) by plate assay methods. A. fumigatus JCM 10253 was selected for extracellular hydrolytic enzymes production under solid-state fermentation. Maximum CMCase (26.2 IU/mL), FPase (18.2 IU/mL), β-glucosidase (0.87 IU/mL), and xylanase (2.6 IU/mL) activities were obtained after incubation time of 144 h at 50 °C. The thermostability of crude cellulase showed the optimum activity at 60 °C and for FPase, β-glucosidase, and xylanase at 50 °C which recommended that the enzymes have a potentially significant role in the biofuel industries. Conclusion The high titer production of active enzymes that cleave different β-1,4-glycosidic bonds still remains a challenge and is the major bottleneck for the lignocellulosic conversion. In particular, the finding of thermostable enzymes which would allow the development of more robust processes is a major goal in this field.